Minimal important changes and differences in elective hand surgery. (November 2015) - Rodrigues, J. N.; Mabvuure, N. T.; Nikkhah, D.; Shariff, Z.; Davis, T. R. C.
Minimal important changes and differences describe the smallest changes and differences between individuals that are relevant to patients following treatment. Minimal important differences may vary between conditions, treatments and lengths of follow-up, and can be calculated in different ways. Minimal important differences for elective hand surgery were reviewed. A total of 99 minimal important differences were identified in 29 articles. The conditions, treatments, outcome measures used and follow-up periods are discussed. The Disabilities of the Arm, Shoulder and Hand had the most estimates of minimal important differences, but these varied. The methods used in the included studies were reviewed and appraised. Most minimal important differences were calculated using retrospective anchors. Future research directions in this area are suggested. Level of evidence: II